REVISITING THE GEOGRAPHICAL INDICATION REGIME IN BANGLADESH: TRIPS COMPATIBILITY AND PROSPECTIVE CHALLENGES (UUM Journal of Legal Studies, 2023)
In the domain ofintellectual property (IP), the Geographical Indication (GI) is deemed to be a sleeping beauty due to its imperial reverberation in consolidating cultural and economic values, particularly in the developing and least developed countries. Bangladesh, being rich in cultural diversities and traditions, has a number of world famous foodstuffs, handicrafts, agricultural products and cultural heritage that could qualify as geographical indications. In this context, the country introduced a sui generis method of GI protection with the promulgation of the Geographical Indications of Goods (Registration and Protection) Act, 2013, which was also monumental in discharging Bangladesh's obligation under the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). The present paper has :firstly chosen to examine the concept of the GI and its legal framework from the IP perspective in order to safeguard both the cultural legacy and genuine producers of geographically exhibiting products of Bangladesh. The key focus of this paper is, however, on the compatibility of TRIPS to Bangladeshi law, particularly inrelation to the aspects of protection and registration of Gls, and to identify the unexplored challenges that the country is supposed to confront as a developing nation. Finally, this article portrays some way-outs to combat potential challenges and help ensure the prospects of Bangladesh in an ever expanding local and global market of GI goods.